Farmer's Institution Performance Of Black Pepper Farmers - Fitriani Fitriani; Sutarni Sutarni (STIE Malangkucecwara, 2014)
Lampung pepper productivity is lower than its potential productivity. These conditions also affect the export performance of Lampung pepper. Efforts to improve the performance of pepper production can not be separated from the pepper growers increase institutional performance itself. Institutional farmer has a central role in efforts to empower farmers. This study aims to analyze the performance of institutional pepper farmers. The study lasted for 4 months from May ? August, 2014. The survey research method involving 40 farmers pepper as respondents in Kecamatan Abung Tinggi Kabupaten Lampung Utara, Lampung. Farmers are members of the farmer unions. Descriptive analysis is used to describe the institutional performance of farmers. The results showed that the farmers were identified institutional farmer groups and Gabunga Farmers Group (union). Institutional pepper farmers have a central role in the development of agibisnis pepper. Institutional performance pepper farmers reflected in the medium category (57%) and (28%) in both categories, namely Gapoktan Prosperous Farmer and Farmer Group Farmer Makmur.